1,2,3-triazolil-1,2,4-oxadiazóis derivados de N-óxidos N-heterocíclicos benzofundidos: síntese, caracterização físico-química, reatividade e estudo computacional - Mayer, João Cândido Pilar (2021)
Taking into account potential bioactive, photophysical and redox-active properties of N-heterocycles and of their N-oxides, a 40 inedit benzofuroxan- or 2,2-dimethyl-2H-benzimidazole-1,3-dioxide- bound 1,2,3-triazolyl-1,2,4-oxadiazoles library was prepared. Employing TBTU as a reagent and DBU as base resulted in a one-pot synthesis with satisfactory yields (49-93%) at room temperature, and in easy purification of the products, followed by characterization by means of 1H and 13C NMR, HRMS and X-ray diffraction. Two examples were reactive towards thiophenol, suggesting that interaction with thiols in biological medium is possible. In both situations, thiophenol was oxidized to its corresponding disulphide, the benzofuroxan derivative displaying selectivity for basic medium. One resulting ortho-dioxime was isolated and characterized, as well as a benzofurazan, its decomposition product. In silico studies at DFT level helped the understanding of benzofuroxan derivatives tautomerization, their geometry and their HOMO and LUMO orbitals. Molecular docking procedures estimated promising interactions between some compounds and the main protease of SARS-CoV-2. Moreover, antimicrobial, cytotoxicity and photophysical/ electrochemical properties of the compounds were carried out in collaboration with other research groups.